Stress effects on microstructure and failure morphology of low carbon steel sheet (2011)
"This paper presents experimental and simulation study of the effects of stress on microstructure and failure morphology of low carbon steel under plane stress conditions. The study has revealed large extension of grains at the point of fracture and, stress and strain looped around the pearlitic faces of the microstructure matrix. The stress and strain distributions in the microstructure have shown that concentration of stress and strain on the pearlite were instrumental to oblique fracture near the constrained region.